2020
DOI: 10.2147/dddt.s284422
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Lactobacillus acidophilus XY27 on DSS-Induced Ulcerative Colitis in Mice

Abstract: Introduction Lactobacillus acidophilus is widely used as probiotic supplement in functional foods due to its beneficial regulatory effects on host, such as immune regulation, anti-inflammatory, and antioxidant activities. Aim This study aimed to determine the preventive effect of Lactobacillus acidophilus XY27 ( L. acidophilus XY27) on colitis induced by dextran sodium. Methods The mice we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…The findings were consistent with 'hygiene hypothesis' which has purported that exposure to certain microbe-enriched environments in the early life stage will contribute to decreasing susceptibility to diseases such as IBD and asthma (Ege et al 2011;Koloski et al 2008). Treatment of mice with DSS, which might induce superficial ulceration, mucosal damage, diarrhoea, rectal bleeding, and loss of body weight, has been used to research the similar clinical symptoms to ulcerative colitis (UC) (Petersson et al 2011;Yan et al 2017;Hu et al 2020). This model is elementary and reproducible and frequently used by its strong, rapid, and dose-dependent UC-like effect.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The findings were consistent with 'hygiene hypothesis' which has purported that exposure to certain microbe-enriched environments in the early life stage will contribute to decreasing susceptibility to diseases such as IBD and asthma (Ege et al 2011;Koloski et al 2008). Treatment of mice with DSS, which might induce superficial ulceration, mucosal damage, diarrhoea, rectal bleeding, and loss of body weight, has been used to research the similar clinical symptoms to ulcerative colitis (UC) (Petersson et al 2011;Yan et al 2017;Hu et al 2020). This model is elementary and reproducible and frequently used by its strong, rapid, and dose-dependent UC-like effect.…”
Section: Resultssupporting
confidence: 77%
“…2017; Cao et al., 2018; Hu et al . 2020). This model is elementary and reproducible and frequently used by its strong, rapid, and dose‐dependent UC‐like effect.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another Lactobacillus strain, Lactobacillus acidophilus, plays a key role in gut homeostasis, mainly through alleviating re-epithelialization and regulating Th17 and Treg immunological cascades [ 18 , 19 , 20 , 21 , 22 ]. Regarding L. acidophilus’ impact on healing, it seems to be commonly used among probiotic mixes with other lactic acid bacteria [ 23 , 24 ], but it is not adequately studied when administered alone, apart from a study by Bahr et al, where it downregulated the expression of TGF-β and α-SMA [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lactic acid bacteria isolated from yak yogurt in pastoral areas are very different from the commonly-used commercial lactic acid bacteria isolated from general yogurt (11,12). Studies have demonstrated that lactic acid bacteria isolated from yak yogurt show better colonization in the intestine, as well as good preventive and interventive effects on colitis and gastritis (13,14) and good regulatory effects on hyperlipidemia (15). As such, these lactic acid bacteria have good biological activity in the body.…”
Section: Introductionmentioning
confidence: 99%